Macro aspects of housing - Charles Ka Yui Leung; Joe Cho Yiu Ng (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This paper aims to achieve two objectives. First, we demonstrate that with respect to business cycle frequency (Burns and Mitchell, 1946), there was a general decrease in the association between macroeconomic variables (MV) and housing market variables (HMV) following the global financial crisis (GFC). However, there are macro-finance variables that exhibited a strong association with the HMV following the GFC. For the medium-term business cycle frequency (Comin and Gertler, 2006), we find that while some correlations exhibit the same change as the business cycle counterparts, others do not. These "new stylized facts" suggest that a reconsideration and refinement of existing "macro-housing" theories would be appropriate. We also provide a review of the recent literature, which may enhance our understanding of the evolving macro-housing-finance linkage.
Keywords: E30; G10; R30; 330; stylized facts; macro-housing-finance linkage; Global Financial Crisis; business cycle frequency; housing market variables